Asset pricing of property sector in Malaysia: the sustainability of shariah compliant status / Nurin Azni Naila Mohd Farouk and Nur Izzah Nasuha Mohd Zaim - Mohd Farouk, Nurin Azni Naila; Mohd Zaim, Nur Izzah Nasuha (2019)
The increase in number of Muslims society globally leads to growing concern regarding the need to involve with Shariah compliant investment. It is evidence by the increase in demand for Shariah compliant product and services in Malaysia. Companies that want to be listed as Shariah compliant need to bare some opportunity cost to meet the Shariah requirement. For instance the company has to consider limited amount of Shariah financing, liquidity as well as the permissible mixed activities. The study aims to examine the stock price for Shariah compliant property companies in Malaysia which are divided into two (2) which are the Shariah sustainable and Shariah non-Sustainable property company. Shariah sustainable represents the company which are able to maintain their Shariah compliant status for the whole sample period. Meanwhile, Shariah non-sustainable company is representing those which are able to maintain the Shariah compliant status for at least 10 announcements before the revised Shariah screening methodology took place but unable to maintain the status after the revision was made. A comparison between the two groups covers 10-year period starting from 2008 to 2017 which consist of 20 announcements of Shariah compliant securities. The study employs Random Effect Model and Fixed Effect Model for Shariah sustainable and Shariah non-sustainable compliant companies respectively. The results of Shariah sustainable shows that firm size, firm value and dividend significantly affect the stock price. However Shariah non-Sustainable reveals only firm value and dividend significantly affect the stock price. The higher coefficient of firm value and dividend for Shariah non-sustainable then Shariah sustainable property company indicates greater stock price for the former group given the increasing of these variables. Therefore, in order for Shariah sustainable to earn similar increment of stock price, the company may need to offer greater firm value and dividend. Although the results reveal that the stock price for Shariah non-sustainable is higher than Shariah sustainable company but the different is statistically insignificant.